Hierarchical folding and reorganization of chromosomes are linked to transcriptional changes in cellular differentiation. Issue 12 (28th December 2015) - Fraser, James; Ferrai, Carmelo; Chiariello, Andrea M; Schueler, Markus; Rito, Tiago; Laudanno, Giovanni; Barbieri, Mariano; Moore, Benjamin L; Kraemer, Dorothee CA; Aitken, Stuart; Xie, Sheila Q; Morris, Kelly J; et al.
Abstract: Mammalian chromosomes fold into arrays of megabase‐sized topologically associating domains (TADs), which are arranged into compartments spanning multiple megabases of genomic DNA. TADs have internal substructures that are often cell type specific, but their higher‐order organization remains elusive. Here, we investigate TAD higher‐order interactions with Hi‐C through neuronal differentiation and show that they form a hierarchy of domains‐within‐domains (metaTADs) extending across genomic scales up to the range of entire chromosomes. We find that TAD interactions are well captured by tree‐like, hierarchical structures irrespective of cell type. metaTAD tree structures correlate with genetic, epigenomic and expression features, and structural tree rearrangements during differentiation are linked to transcriptional state changes. Using polymer modelling, we demonstrate that hierarchical folding promotes efficient chromatin packaging without the loss of contact specificity, highlighting a role far beyond the simple need for packing efficiency. Synopsis: Genome‐wide mapping of chromatin architecture reveals a hierarchical folding of chromatin that involves higher‐order domains interactions across the whole chromosomes, reflects epigenomic features and reorganizes upon differentiation‐induced gene expression changes. Chromatin architecture is mapped genome‐wide using Hi‐C and a neuronal differentiation model from mESC to post‐mitotic neurons. Mammalian chromosomes fold hierarchically in a manner that reflects epigenomic features and involves higher‐order domains (metaTADs) up to the chromosome scale. metaTAD topologies are relatively conserved through differentiation, and their reorganization is related to gene expression changes. Polymer modelling shows that hierarchical chromatin folding promotes efficient packaging without the loss of contact specificity. Abstract : Genome‐wide mapping of chromatin architecture reveals a hierarchical folding of chromatin that involves higher‐order domains interactions across the whole chromosomes, reflects epigenomic features and reorganizes upon differentiation‐induced gene expression changes.